2018
DOI: 10.1002/wnan.1543
|View full text |Cite
|
Sign up to set email alerts
|

Targeted siRNA delivery using aptamer‐siRNA chimeras and aptamer‐conjugated nanoparticles

Abstract: The sequence-specific gene-silencing ability of small interfering RNA (siRNA) has been exploited as a new therapeutic approach for the treatment of a variety of diseases. However, efficient and safe delivery of siRNA into target cells is still a challenge in the clinical development of siRNA-based therapeutics. Recently, nucleic acid-based aptamers that target cell surface proteins have emerged as a new class of targeting moieties due to their high specificity and avidity. To date, various aptamer-mediated siR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 111 publications
0
21
0
Order By: Relevance
“…ShRNA technology has obvious advantages over siRNA technology in that optimized shRNA constructs possess high potency and sustainable effects using low copy numbers and eliminates off‐target effects, which has been demonstrated in multiple studies . Recently, shRNA technology has been highly appreciated and attracted growing attention, and a new research paradigm for clinical gene therapy was built based on this technology . In this study, shRNA interference successfully and effectively block the expression of Piezo1 at the gene level, suggesting an advantage over the inhibitor GsMTx4.…”
Section: Discussionmentioning
confidence: 75%
“…ShRNA technology has obvious advantages over siRNA technology in that optimized shRNA constructs possess high potency and sustainable effects using low copy numbers and eliminates off‐target effects, which has been demonstrated in multiple studies . Recently, shRNA technology has been highly appreciated and attracted growing attention, and a new research paradigm for clinical gene therapy was built based on this technology . In this study, shRNA interference successfully and effectively block the expression of Piezo1 at the gene level, suggesting an advantage over the inhibitor GsMTx4.…”
Section: Discussionmentioning
confidence: 75%
“…Aptamers are also used for targeted delivery of drugs and other genetic elements, such as siRNAs, to cells (18)(19)(20). siRNAs are reliable gene knockdown tools.…”
Section: Rationalementioning
confidence: 99%
“…There is the possibility of target specificity, RNAi efficacy, and stability of siRNA-aptamers chimeras being affected by chemical modifications. Therefore, it is crucial to find an optimal alternative for each siRNA aptamers chimera to maximize its therapeutic efficacy [38].…”
Section: Aptamer In the Delivery Of Therapeutic Nanoparticles Containmentioning
confidence: 99%
“…Furthermore, it has been shown that PEG formulation reduces immune responses in vivo [41]. The thermal stability of siRNA is another parameter to be considered in gene silencing activity when it is conjugated to aptamers [38]. In this context, the computational modeling has been used to guide RNA aptamer truncations, maintaining their functionality, and preventing and minimizing therapy challenges using siRNA.…”
Section: Aptamer In the Delivery Of Therapeutic Nanoparticles Containmentioning
confidence: 99%